2016
DOI: 10.1002/cncr.30327
|View full text |Cite
|
Sign up to set email alerts
|

Impact of facility volume on outcomes in patients with squamous cell carcinoma of the anal canal: Analysis of the National Cancer Data Base

Abstract: Treatment at higher volume radiation oncology centers appears to be associated with improved OS in patients with SCC of the anal canal. These results likely reflect the relation between physician experience and delivery of high-quality RT, which perhaps is best evident in rare tumors such as anal SCC. Cancer 2017;123:228-236. © 2016 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 40 publications
3
33
2
Order By: Relevance
“…Treatment facilities treating 3 or fewer cases over the time period examined appeared to have worse overall survival compared to centers with more experience. These findings are similar to other studies which demonstrate that patients who receive cancer treatment at lower volume centers have worse survival outcomes [4,8,[15][16][17][18][19][20][21][22]. The majority of these studies, however, tend to report on the relationship between hospital and surgical volume with outcomes [6,[15][16][17][18][19]23], and there are fewer studies investigating radiation or concurrent chemoradiation therapy [4,10,24].…”
Section: Discussionsupporting
confidence: 86%
“…Treatment facilities treating 3 or fewer cases over the time period examined appeared to have worse overall survival compared to centers with more experience. These findings are similar to other studies which demonstrate that patients who receive cancer treatment at lower volume centers have worse survival outcomes [4,8,[15][16][17][18][19][20][21][22]. The majority of these studies, however, tend to report on the relationship between hospital and surgical volume with outcomes [6,[15][16][17][18][19]23], and there are fewer studies investigating radiation or concurrent chemoradiation therapy [4,10,24].…”
Section: Discussionsupporting
confidence: 86%
“…[37] Given the well-established relationship between hospital characteristics, such as operative volume and teaching status with improved outcomes among patients with cancer, there have been increased efforts by policymakers and hospital administrators within the United States to promote regionalization of care for complex surgical conditions. [14,43,44] [45,46] The relative impact of insurance status on regionalization of care to major, urban teaching hospitals has not, however, been wellstudied. In the current study, compared with privately insured patients, individuals who were insured by Medicaid were at a markedly decreased odds of undergoing surgery for HP cancers at urban non-teaching (OR 0.36) and urban teaching hospitals (OR 0.54).…”
Section: Discussionmentioning
confidence: 99%
“…Volume-outcome analyses evaluating nonsurgical cancer outcomes are scarce and have primarily focused on hospital-level case volume and overall survival for select malignancies, [36][37][38][39] including NHL. 37 More recently, our group found that Medicare beneficiaries with newly diagnosed DLBCL were more likely to receive standard immunochemotherapy and have better survival when managed by oncologists with greater experience treating older adults with lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with previous analyses evaluating facility-level volume-outcome relationships in cancer, wherein treatment details were limited. [36][37][38][39]42 Finally, we included physician-level variables from the AMA Physician Masterfile to minimize unmeasured variables that could have influenced the study findings.…”
Section: Discussionmentioning
confidence: 99%